Peran identitas diri sebagai mahasiswa dalam pembentukan karakter bermoral dan religius melalui kajian agama - Muti, Farah Auliya (Maliki Interdisciplinary Journal, 2025)
Student character building is a crucial aspect in higher education, especially in facing the challenges of globalization and moral crisis. This research aims to examine the role of religious studies in shaping students’ self-identity and its contribution to the formation of moral and religious character. Religious studies is seen as a strategic approach because it prioritizes ethical values, spirituality, and nationality. Through a deep and reflective approach, this activity is expected to strengthen the spiritual awareness and moral integrity of students as future agents of social change. This research may provide a new perspective in developing character education in higher education. The results of this study show that the active involvement of students in religious studies is able to increase spiritual awareness, strengthen moral values, and form a self-identity that is in line with religious and national values. Religious studies are also an effective forum for reflection in fostering empathy, social responsibility, and a spirit of positive contribution to society. Thus, strengthening religious studies in higher education can be a strategic solution in developing holistic and sustainable character education. This research is expected to provide a conceptual contribution for policy makers and educational practitioners in designing character development programs based on religious values.